Financial Reforms and Corporate Financing Decisions of Indian Industries - Jadiyappa, Nemiraja; Nagi Reddy, V. (Indian Journal of Finance, 2014)
This study evaluates the impact of financial reforms on the corporate financing decisions of selected 23 Indian industries for the period from 1988-2005. We used a financial reforms index that will allow a better understanding of the impact of gradual reforms on the corporate financing decisions. Our findings from the pooled regression indicate that the impact of financial reforms is negative for most of the industries. However, a significant difference is observed in the manner in which these industries reacted to counter this negative impact. The decline in the leverage ratio was offset by a corresponding increase in external equity proportion in the case of a few industries, and by an appreciation in the internal capital proportion for the remaining industries. Finally, our results do not support the hypothesis that interest rate is the main route through which the impact of macro-level financial reforms is experienced at the micro-level.